Persistent incentives to learn: experimental evidence from Brazil - Neri, Guilherme de Almeida (2022)
Financial incentives linked to test performance have been a topic of study in contexts where they exist only for a single test or year. This paper explores a policy's randomized setting in which monetary rewards are attached to exams for multiple years, with the control group never being incentivized. I link the program's rich administrative data with that of a separate set of non-incented math and language exams spanning four consecutive years. Firstly, no effects on grade retentions and small ones on exam abstentions are found. Regarding tests scores, results show no impact in the first year, suggesting evidence from previous literature of immediate effects in incented tests may not reflect students' cognitive development. For the second year, positive impacts emerge, opposing the notion that financial rewards contemporaneously crowd out intrinsic motivation. For the third and final years, although incentives persist, the effects do not, gradually fading away in language and instantly disappearing in math.